Chromosome 11q loss and MYCN amplification demonstrate synthetic lethality with checkpoint kinase 1 inhibition in neuroblastoma - Keller, Kaylee M.; Eleveld, Thomas F.; Schild, Linda; van den Handel, Kim; van den Boogaard, Marlinde; Amo-Addae, Vicky; Eising, Selma; Ober, Kimberley; Koopmans, Bianca; Looijenga, Leendert; Tytgat, Godelieve A.M.; Ylstra, Bauke; et al. (Frontiers in Oncology, 2022)
Neuroblastoma is the most common extracranial solid tumor found in children and despite intense multi-modal therapeutic approaches, low overall survival rates of high-risk patients persist. Tumors with heterozygous loss of chromosome 11q and MYCN amplification are two genetically distinct subsets of neuroblastoma that are associated with poor patient outcome. Using an isogenic 11q deleted model system and high-throughput drug screening, we identify checkpoint kinase 1 (CHK1) as a potential therapeutic target for 11q deleted neuroblastoma. Further investigation reveals MYCN amplification as a possible additional biomarker for CHK1 inhibition, independent of 11q loss. Overall, our study highlights the potential power of studying chromosomal aberrations to guide preclinical development of novel drug targets and combinations. Additionally, our study builds on the growing evidence that DNA damage repair and replication stress response pathways offer therapeutic vulnerabilities for the treatment of neuroblastoma.